Analysis of Radiation‐Induced Changes in Cell Cycle and DNA Damage of Murine Hematopoietic Stem Cells by Multi‐Color Flow Cytometry. Issue 8 (16th August 2021) - Majumdar, Debajyoti; Pietras, Eric M.; Pawar, Snehalata A.
Abstract: Exposure of bone marrow to genotoxic stress such as ionizing radiation (IR) results in a rapid decline of peripheral blood cells and stimulates entry of the normally quiescent hematopoietic stem cells (HSCs) into the cell cycle to reconstitute the hematopoietic system. While several protocols have employed flow cytometry analysis of bone marrow cells to study changes in specific cell populations with respect to cell cycle proliferation and/or expression of γ‐H2AX, a marker of DNA damage, these parameters were examined in separate panels. Here, we describe a flow cytometry‐based method specifically designed to examine cell cycle distribution using Ki‐67 and FXCycle violet in combination with γ‐H2AX in HSCs and hematopoietic progenitor cells (HPCs) within the same sample. This method is very useful, particularly in studies involving genotoxic stresses such as IR, which substantially reduce the absolute numbers of HSCs and HPCs available for staining. Additionally, we describe several important considerations for the analysis of markers of HSCs in irradiated versus unirradiated samples. Examples include the use of fluorescence minus one (FMO) controls, the gating strategy for markers whose expression is typically impacted by IR such as Sca1, tips for staining of intracellular antigens like Ki67, and ensuring the detection of signal from at least 500 events in each gate to ensure robustness of the results. © 2021 Wiley Periodicals LLC. Basic Protocol : Immunostaining protocol for bone marrow mononuclear cells using a multi‐fluorophore panel